2017
DOI: 10.1371/journal.pone.0178676
|View full text |Cite
|
Sign up to set email alerts
|

The impact of de novo liver metastasis on clinical outcome in patients with advanced non-small-cell lung cancer

Abstract: Liver metastasis has been found to affect outcome in prostate cancer and colorectal cancer, but its role in lung cancer is unclear. The current study aimed to evaluate the impact of de novo liver metastasis (DLM) on stage IV non-small cell lung cancer (NSCLC) outcomes and to examine whether tyrosine kinase inhibitors (TKI) reverse poor prognosis in patients with DLM and epidermal growth factor receptor (EGFR)-mutant NSCLC. Among 1392 newly diagnosed NSCLC patients, 490 patients with stage IV disease treated be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Our two studies were different in the patient cohorts, genetic backgrounds and chemotherapeutic regimens. LMR has been demonstrated as a prognostic factor for OS and PFS of advanced stage patients with non-specific NSCLC [ 13 , 27 ] and NSCLC with positive EGFR mutation [ 28 ] ( Table 5 [ 13 , 26 - 28 ]). On the other hand, six studies showed GPS as a prognostic factor for advanced stage of non-specific NSCLC [ 15 , 16 , 29 - 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our two studies were different in the patient cohorts, genetic backgrounds and chemotherapeutic regimens. LMR has been demonstrated as a prognostic factor for OS and PFS of advanced stage patients with non-specific NSCLC [ 13 , 27 ] and NSCLC with positive EGFR mutation [ 28 ] ( Table 5 [ 13 , 26 - 28 ]). On the other hand, six studies showed GPS as a prognostic factor for advanced stage of non-specific NSCLC [ 15 , 16 , 29 - 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous multivariate analyses, LMR, but not NLR, was an independent prognostic factor for advanced adenocarcinoma with wild-type epidermal growth factor receptor (EGFR). Two previous studies for advanced and unselected NSCLC [ 12 , 20 ] and another study for advanced EGFR-mutated NSCLC treated with EGFR tyrosine kinase inhibitors (TKIs) [ 21 ] detected LMR as independent prognostic factors for OS. On the contrary, according to another our study of patients with NSCLC harboring activated EGFR mutation who had been treated with EGFR-TKIs, NLR, but not LMR, was an independent prognostic factor for this selected population.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that patients with NSCLC with multi-site metastases exhibit worse outcomes than patients with a single metastatic site (9). Additionally, some studies have observed poor survival in patients with liver metastasis (10,11). However, for the majority of these studies, the main limitation was that the sample size was too small.…”
Section: Introductionmentioning
confidence: 99%